2016
DOI: 10.5294/aqui.2016.16.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de úlceras venosas na qualidade de vida de indivíduos atendidos na atenção primária

Abstract: Objetivo: analisar o impacto das úlceras venosas (UV) na qualidade de vida (QV) das pessoas atendidas na atenção primária à saúde. Material e método: pesquisa quantitativa, descritiva e transversal, realizada com 101 usuários, atendidos em 42 serviços de saúde de Natal, Rio Grande do Norte, Brasil. Os dados foram coletados de fevereiro a setembro de 2014, por meio de um questionário sociodemográfico, clínico e de saúde, e do Charing Cross Venous Ulcer Questionnaire. Utilizou-se estatística descritiva e inferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
15

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 19 publications
1
20
0
15
Order By: Relevance
“…In addition to the tissue changes associated with aging, the possibility of comorbidities, immobility and malnutrition exists in the elderly (21) . The period of skin lesions is directly related to the quality of life of these users, longer lesion time refers to lower quality of life (22) . Research on leg ulcers showed that the majority of those assessed resided only with their spouse or with another family member.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the tissue changes associated with aging, the possibility of comorbidities, immobility and malnutrition exists in the elderly (21) . The period of skin lesions is directly related to the quality of life of these users, longer lesion time refers to lower quality of life (22) . Research on leg ulcers showed that the majority of those assessed resided only with their spouse or with another family member.…”
Section: Discussionmentioning
confidence: 99%
“…O fumo e o álcool também podem ser considerados fatores de risco, pois o primeiro produz efeitos no organismo que interferem no fluxo sanguíneo, provocando vasoconstrição, favorecendo a diminuição do aporte de oxigênio e nutrientes para as células, e o segundo pode ocasionar lesão de células neuronais, de sistema cardíaco, células hepáticas e pancreáticas (21) .…”
Section: Métodounclassified
“…When investigating the association between the VU time, there was worst mean on those people over 1 year of injury, and the emotional state and aesthetics were significantly affected [15]. In another study, the risk factors and pathological personal antecedents were more present in people with treatment time greater than 1 year [22].…”
Section: Sociodemographic Clinical and Care Influence In The Healinmentioning
confidence: 99%
“…Studies show the prevalence and association of these diseases in people with VU [14,15], which makes them difficult aspects of healing. The hypertension is often associated with atherosclerosis and Diabetes can lead to complications in the skin as a result of neuropathy, also, to often be associated with peripheral arterial disease, making the stabilization of the injury.…”
Section: Sociodemographic Clinical and Care Influence In The Healinmentioning
confidence: 99%